Control of Epstein-Barr Virus (EBV) in the Oral Cavity Is Associated With Persistence of Oral Human Papillomavirus (HPV)16/18 Among Men From the HPV Infection in Men Study. (9th June 2022) - Dickey, Brittney L; Giuliano, Anna R; Sirak, Bradley; Abrahamsen, Martha; Lazcano-Ponce, Eduardo; Villa, Luisa L; Coghill, Anna E
Abstract: Background: Human papillomavirus (HPV)-related oropharyngeal cancer (OPC) incidence is increasing among men. Biomarkers that can identify oral HPV16/18 infections likely to persist, the obligate precursor for HPV-OPC, are needed. Methods: We assessed the association between oral Epstein-Barr virus (EBV) and oral HPV16/18 persistence among 63 men in the HPV Infection in Men Study who tested positive for HPV16/18 at the baseline visit. Control of oral coinfections, including EBV, could serve as a biomarker of immune competence and the ability to control oral HPV. Results: Detection of oral EBV was significantly associated with oral HPV16/18 ≥12-month persistence. Conclusions: Detection of oral EBV deserves evaluation as a biomarker for oral HPV persistence and HPV-related OPC. Abstract : Detection of oral EBV shedding was significantly associated with the persistence of an oral HPV16/18 infection to at least 12 months. EBV coinfection therefore deserves further evaluation in its association with oral HPV persistence.